Espèces de Liolaemus sans pores précloacaux chez les mâles, le long des Andes méridionales (Reptilia: Squamata: Iguania: Tropiduridae) - Videla, Fernando (1998)
Our last findings in Cordilleran mountains of the Malargue Deparment, Southern Mendoza Province, Argentina, led us to evaluate the lack of secretory precloacal pores in Liolaemus males, considering it as a noticeable evolutionary trend of peculiar species groups, rather than a somewhat occasional morpho-physiological character (absence of pheromones?) occurring at random in different taxa of the same phyletic line, as in its usual interpretation. In fact, our recent discovery of a new species of Liolaemine iguanid whitout precloacal pores (Liolaemus thermarum Videla et Cei, 1996) in the basaltic landscape (2400 m) surrounding the Peteroa Volcano (4135 m) gave us the chance of a wide screening of all its nearly related forms also missing this important secondary sex character (Figs 1-4). Only four species, belonging to a major “chiliensis” group, very similar to L. thermarun for their somatic features, presented a total lack of precloacal pores, in the Andean and sub-Andean environments along the Chilean-Argentine frontier, between 35° and 40° South Latitude (Fig. 2). Striking biogeographical and ecological remarks point out the actual scattering of all these taxa mainly in the distribution area of the preglacial coniferous woods, such as Araucaria araucana formations. That is the case of Liolaemus neuquensis in the neighbourhood of the Copahue Volcano (1800 m) and of L. coeruleus from the basaltic relief of Primeros Pinos and Lonco Luan (1800) also in Neuquen Province, Argentina. Liolaemus thermarum and L. cristiani (Cerro El Peine, 2248 m, Maule, Chile) live now in biotopes wanting relics of the ancestral Araucaria woods, but their precursors can to have been likely in touch with this spread ecosystem during the long period of their quaternary isolation (see Fig. 5). According to our screening, another austral species group of Liolaemus showing the above mentioned peculiar lack of precloacal pores in males could be also put in evidence from 46° to 50° S.Lat. (Figs 2, 4). They are the lineomaculatus and “silvanae” groups (Fig. 2), spreading the first with only a species from the Atlantic coast to the Cordillerans, living the second in a very specialized periglacial habitat of Santa Cruz Province, Argentina, with the endemic Liolaemus silvanae from the flat summit (1400 m) of the isolated Meseta de la Laguna del Sello, near the great Patagonian ice field, and with the very localized L. periglacialis in some tabulated, broken sub-Andean basaltic embossments, also at the latitude of the continental inland ice still remnant alongside the Pacific borders. Conclusions of the present research were that the lack of precloacal pores in males was only proved in the here reported Liolaemus groups living under hard, cold environmental conditions, from the Southern Andrean valleys at about 35° - 40 °S Lat. to the most extreme periglacial habitats. Any speculation concerning the adaptive value of such a likely derived character lies yet opaque, and a further more detailed research is needed. We point out that no other species of Liolaemus exhibit apparently such a morphological condition. Any former bibliographic report about other taxa from other groups does not provide a suitable information, being often supported by some misleading understanding of the original species descriptions.